2020
DOI: 10.3390/catal10040413
|View full text |Cite
|
Sign up to set email alerts
|

NaBiS2 as a Novel Indirect Bandgap Full Spectrum Photocatalyst: Synthesis and Application

Abstract: Photocatalysts with a superior activity range, from ultraviolet (UV) to near-infrared (NIR) light, are attractive for solar utilization. From this perspective, sulfides are promising due to their narrower bandgap than oxides. In this report, NaBiS 2 was synthesized hydrothermally under mild conditions by adjusting the alkaline amount. The rough NaBiS 2 nanosheets possessed various surface atomic configurations on their surfaces, including amorphous clusters and amorphous nano-domains, revealed by HRTEM. A theo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…However, if ions also migrate under applied bias and accumulate at the interfaces between NaBiS 2 and the transport layers, a large excess charge‐carrier gradient might be induced in the vicinity of the interface, which could introduce extra interface recombination and hence reduce the quasi‐Fermi level splitting. [ 35,36 ] We can see from Figure 5b that there is indeed a reduction in the V OC of the LiI‐treated NaBiS 2 device under continuous light illumination, dropping from 0.31 V to almost 0 V after only 100 s at open‐circuit. For reference, the V OC evolution of a typical AgBiS 2 device under the same experimental conditions was also recorded, which only dropped by approximately 10 meV during the same period, as displayed by the black dots in Figure 5b.…”
Section: Resultsmentioning
confidence: 96%
“…However, if ions also migrate under applied bias and accumulate at the interfaces between NaBiS 2 and the transport layers, a large excess charge‐carrier gradient might be induced in the vicinity of the interface, which could introduce extra interface recombination and hence reduce the quasi‐Fermi level splitting. [ 35,36 ] We can see from Figure 5b that there is indeed a reduction in the V OC of the LiI‐treated NaBiS 2 device under continuous light illumination, dropping from 0.31 V to almost 0 V after only 100 s at open‐circuit. For reference, the V OC evolution of a typical AgBiS 2 device under the same experimental conditions was also recorded, which only dropped by approximately 10 meV during the same period, as displayed by the black dots in Figure 5b.…”
Section: Resultsmentioning
confidence: 96%
“…Rosales et al reported the synthesis of the NaBiS 2 nanoparticles using a solution-phase method . The hydrothermal preparations of NaBiS 2 nanosheets (NSs) and NaBiS 2 nanoribbons were reported by Wang et al and Guo et al, respectively. , Compared with these 0D, 1D or 2D nanostructures, three-dimensional (3D) materials have several fascinating merits including a high surface-to-volume ratio, unique multidimensional morphology, and the combination of micro-nanoscales. , In particular, the 3D hierarchical structure with NS building blocks has significant benefits in the light-harvesting and antiaggregation capability. Therefore, assembling NaBiS 2 with a 3D hierarchical structure into the photodetector is expected to result in excellent detection performance in the wavelength range from UV to IR. However, there are few studies on the preparation of NaBiS 2 with a 3D hierarchical structure, which is not frequently applied in the photodetector field.…”
Section: Introductionmentioning
confidence: 99%
“…11 Rosales et al reported the synthesis of the NaBiS 2 nanoparticles using a solution-phase method. 12 The hydrothermal preparations of 13,14 Compared with these 0D, 1D or 2D nanostructures, threedimensional (3D) materials have several fascinating merits including a high surface-to-volume ratio, unique multidimensional morphology, and the combination of micro-nanoscales. 15,16 In particular, the 3D hierarchical structure with NS building blocks has significant benefits in the lightharvesting and antiaggregation capability.…”
Section: Introductionmentioning
confidence: 99%